Augmented Reality-Based Comic Media: A Metacognitive Approach to Enhance Cultural Literacy and Reading Engagement in Elementary Education - Pratiwi, Ni Komang Desi; Bayu, Gede Wira (International Journal of Elementary Education, 2024)
Declining reading engagement and low cultural literacy are key issues in 4th grade of elementary school. This study aims to develop an Augmented Reality (AR)-based comic learning media that highlights the cultural diversity of Bali, focusing on metacognitive learning to enhance students' cultural literacy and reading engagement. The study also analyzes the media's content validity, students' responses to the media, and the media's effectiveness in improving cultural literacy and reading engagement. This research employs the ADDIE model, with the AR-based comic media as the subject, and the research object covering the validity, practicality, and effectiveness of the media. Data was collected via student questionnaires and teacher interviews, with validity tested using the CVR formula and analysis conducted via a correlated t-test in SPSS. The results indicate that the AR-based comic learning media has a high level of validity, covering content validity, media validity, and instructional design. Students found the media practical and highly effective in boosting cultural literacy and reading engagement. Statistical test results show significance values (sig.) for cultural literacy and reading engagement of <0.001, with Fcalculated > Ftable, indicating that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. It can be concluded that, AR-based comic media innovation can support the learning process and help teachers in delivering learning materials more interestingly and effectively, and can increase cultural literacy and student reading engagement. This study has implications for increasing the availability of more diverse and technology-based learning media.